Reimagining Islamic Educational Leadership; The Integrative Leadership Style of Kyai in Pesantren-based Higher Education Institution - Akmal Mundiri; Faiq Julia Iqna’a (JURNAL ISLAM NUSANTARA, 2025)
This research examines the dynamics of integrative leadership at Ma'had Aly Nurul Jadid, particularly how a leader not only performs managerial functions but also maintains a scholarly presence through direct involvement in the tradition of transmitting “Kitab Kuning”s. The purpose of this research is to provide a comprehensive understanding of integrative leadership behaviour. The research used a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation. The collected data were analysed using Miles and Huberman's data analysis technique, which consists of data reduction, data display, and verification/conclusion drawing. The results show that integrative leadership behaviour at Ma'had Aly is manifested in the leader's willingness to internalise the Amanah value, exemplary and moral will in implementing the sorogan tradition, and epistemic anxiety that drives the development of a scientific literacy movement. This research has implications for strengthening the concept of values-based Islamic educational leadership, particularly in the dimensions of epistemic leadership and cultural leadership. Thus, these findings indicate that effective Islamic boarding school leadership is not a dichotomy between bureaucracy and science, but rather an integration of both within a single figure who can maintain tradition while managing modern institutional demands.